The Distinctive Features of the Navoi Style - Tolibjon Ruziboev (International Journal Of Literature And Languages, 2026)
This article examines specific aspects of the use of poetic art in literary texts, related to the study of classical Uzbek poetics. This topic is illustrated using the work of Alisher Navoi as an example. One of the poet's ghazals is analyzed, and the poetic techniques used in it and their significance in revealing the theme and ideological content of the work are discussed. The article also provides a detailed analysis of Alisher Navoi's mastery of the artistic medium and his unique creative style.